Instrument for measuring maternal attitudes, knowledge and self-confidence towards breastfeeding: Literature review - Rosyidah, Hanifatur; Nafisah, Wardatun; Surani, Endang; Nakatudde, Hadijah (Journal of Health Technology Assessment in Midwifery, 2024)
The level of exclusive breastfeeding in Indonesia has still not reached the expected target. According to the World Health Organization (WHO), in 2019 the average rate of exclusive breastfeeding in the world was around 38%. This is far above the target of 50%. The causes of low coverage of exclusive breastfeeding are influenced by lack of awareness of the importance of breastfeeding, lack of maternal self-confidence, and low knowledge about the benefits of breastfeeding for mothers and babies. The research aims to describe and compare breastfeeding assessment instruments which include assessing mothers' attitudes, knowledge and beliefs in exclusive breastfeeding. The method used in this review is identification based on keywords, screening titles and abstracts, and selecting based on inclusion and exclusion criteria. The total of 10 articles were reviewed. According to 10 articles, 7 instruments were obtained, such as NeoEAT-Breastfeeding and IIFAS, which are effective in assessing the attitudes, knowledge, and beliefs of breastfeeding mothers. Overall, the instruments mentioned above can be used by healthcare workers to assess a mother's ability to breastfeed, with the note that validation and adaptation of the instrument into the national language are required.